2009
DOI: 10.1016/j.eneco.2008.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Investment and upgrade in distributed generation under uncertainty

Abstract: The ongoing deregulation of electricity industries worldwide is providing incentives for microgrids to use small-scale distributed generation (DG) and combined heat and power (CHP) applications via heat exchangers (HXs) to meet local energy loads. Although the electric-only efficiency of DG is lower than that of central-station production, relatively high tariff rates and the potential for CHP applications increase the attraction of on-site generation. Nevertheless, a microgrid contemplating the installation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Indeed, a ceteris paribus increase in the subsidy raises the value of the lumpy investment strategy, as it is relatively cheaper than stepwise investment. However, with discretion over capacity, a firm compensates for the extra cost associated with the flexibility to proceed in stages by increasing the amount of installed capacity , and, thus, in contrast to Siddiqui and Maribu (2009) and Kort et al (2010), stepwise investment always dominates a lumpy investment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a ceteris paribus increase in the subsidy raises the value of the lumpy investment strategy, as it is relatively cheaper than stepwise investment. However, with discretion over capacity, a firm compensates for the extra cost associated with the flexibility to proceed in stages by increasing the amount of installed capacity , and, thus, in contrast to Siddiqui and Maribu (2009) and Kort et al (2010), stepwise investment always dominates a lumpy investment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Some use the real options approach (Dixit and Pindyck 1994), which is able to handle uncertainty, discretion over timing, and multi-stage problems. However, in order to obtain quasi-analytical solutions, simplifying assumptions are usually made about the underlying uncertainties (Siddiqui and Maribu 2009). Furthermore, risk is not directly addressed in the objective function even in simulation-based studies that accommodate more realistic price processes because the objective is still to maximise expected profit (Abadie and Chamorro 2008).…”
Section: Related Workmentioning
confidence: 99%
“…Predictably, studies concerning the impact of fuel price uncertainty show that the risk of investment increases as the volatility of fuel price increases [18]. It has also been shown that payback is more likely to increase than decrease when faced with electric rate, fuel price, or capital cost volatility [19].…”
mentioning
confidence: 99%